Increased myocardial [123I]-metaiodobenzylguanidine uptake after enalapril treatment in patients with chronic heart failure. - Somsen, G. A. (1996)
OBJECTIVE: To assess non-invasively the effect of enalapril on cardiac sympathetic neuronal uptake function in patients with congestive heart failure, by using [123I]-metaiodobenzylguanidine (MIBG), which is a noradrenaline analogue. Cardiac MIBG uptake was visualised by single photon emission tomography (SPET). In addition, plasma noradrenaline concentration, indicating systemic sympathetic activity, was measured to see whether it was related to cardiac MIBG uptake. DESIGN: Consecutive patients were treated with enalapril and served as their own controls. SETTING: Cardiac unit of a tertiary care centre. PATIENTS: 23 Patients with chronic, mild to moderate, stable congestive heart failure, and a left ventricular ejection fraction less than 40%. Heart failure was caused by ischaemic heart disease or was idiopathic. INTERVENTIONS: Cardiac MIBG SPET was performed and plasma noradrenaline concentration was measured before and after 6 weeks treatment with enalapril. MAIN OUTCOME MEASURES: Cardiac uptake of MIBG was measured by using the left ventricular cavity and a venous blood sample as a reference. RESULTS: Cardiac uptake of MIBG increased significantly after enalapril treatment, indicating improved cardiac neuronal uptake function. Plasma noradrenaline concentration did not decrease significantly. Cardiac MIBG uptake was not related to plasma noradrenaline concentration. CONCLUSIONS: Cardiac MIBG SPET can be used to assess changes in cardiac sympathetic neuronal uptake function caused by pharmacological intervention. Enalapril seemed to improve cardiac sympathetic neuronal uptake function but did not significantly affect plasma noradrenaline concentrations in a group of patients with predominantly moderate heart failure. These results accord with the hypothesis that restoration of cardiac neuronal uptake of noradrenaline is one of the beneficial effects of enalapril in such patients.